Towards feasibility and sustainability of chrysanthemum cut flowers farming: Evidence from Pasuruan Regency, Indonesia - Silvi Purnama Sari; Iwan Nugroho; Rita Hanafie; Suwarta Suwarta (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2022)
The chrysanthemum commodity has shown a marked increase in the demand for decorations, ornaments and ceremonies service business in urban areas. This has raised attention to the feasibility and implications of sustainable production at the farm level. This study aims to measure the economic feasibility and sustainability of the chrysanthemum farm business. The study was carried out by surveying 24 chrysanthemum farmers in the village of Tutur, Tutur District, Pasuruan Regency. The analysis method used farming feasibility and multidimensional scaling (MDS) approach of Rapfish. The results of the study found the criteria for chrysanthemum cultivation of R/C ratio and ROI of 2.58 and 1.58, with profit equivalent to 126.66 million rupiahs per month per hectare. The study also found that the sustainability index in the dimensions of the social, economic, institutional, and environment was 62.74, 57.76, 57.48 and 51.66; all of which are categorized as fairly sustainable. In those dimensions, it was found that the most important attributes influencing sustainability were land conversion, farmers' network in chrysanthemum cultivation, access to business capital and changes in market trends. Further research suggests strengthening farmer group institutions, implementing innovation and developing sustainable tourism areas.JEL Classification  F18; Q13; Q18